Effects of dietary geniposidic acid on growth performance, flesh quality and collagen gene expression of grass carp, Ctenopharyngodon idella. (21st December 2017) - Sun, W.T.; Xu, X.Y.; Li, X.Q.; Pan, W.Q.; Leng, X.J.
Abstract: This study was conducted to investigate the effects of dietary geniposidic acid (GA) on growth performance, flesh quality and collagen gene expression of grass carp ( Ctenopharyngodon idella ). The fish with an initial body weight of 47.1 ± 0.8 g were fed one of the seven diets, including control diet, Eucommia ulmoides (EU)‐supplemented diet (20 g/kg) and GA‐supplemented diets (200, 400, 600, 800 and 1, 000 mg/kg GA) for 75 days. The growth performance and muscle proximate composition showed no difference among groups ( p > .05). Dietary GA (200–1, 000 mg/kg) increased the contents of total collagen and alkaline‐insoluble collagen in skin ( p < .05), and high supplementation of GA (600–1, 000 mg/kg GA) and EU increased the contents of total collagen, alkaline‐insoluble collagen and total amino acids ( p < .05), but reduced the lipid level in muscle ( p < .05). In collagen gene expression, EU and 200–1, 000 mg/kg GA increased COL1A1 expression in muscle and skin ( p < .05), but the expression of COL1A2 was increased only by high supplementation of GA (1, 000 mg/kg, or 800–1, 000 mg/kg) ( p < .05). In conclusion, dietary GA improved the flesh quality of grass carp, and the supplementation level was estimated to be 600 mg/kg diet.